To solve this expression, we can apply the properties of operations and rules for multiplying and dividing.
To start, let's simplify the multiplication first:
(-2) × (15) × (-56) = 1680
Now, let's solve the division:
1680 ÷ 23 ÷ 34
By using the division property, we can perform the divisions from left to right:
1680 ÷ 23 = 73.04347826...
73.04347826... ÷ 34 = 2.147058823...
Therefore, (-2) × (15) ÷ (23) × (-56) ÷ (34) simplifies to approximately 2.147058823.
Use the properties of operations and rules for multiplying and dividing to solve:
(−2)×(15)÷(23)×(−56)÷(34)
one point
34 answers
Use the properties of operations and rules for multiplying and dividing to solve:
(−2)×(1/5)÷(2/3)×(−5/6)÷(3/4)
(−2)×(1/5)÷(2/3)×(−5/6)÷(3/4)
To solve this expression, we can use the properties of operations and rules for multiplying and dividing. Let's simplify it step by step:
First, let's simplify the multiplication:
(-2) × (1/5) × (-5/6) = (-2) × (-1) × (1/5) × (5/6) = 2/6 = 1/3
Now, let's solve the division:
(1/3) ÷ (2/3) ÷ (3/4)
By using the division property, we can perform the divisions from left to right:
(1/3) ÷ (2/3) = (1/3) × (3/2) = 3/6 = 1/2
(1/2) ÷ (3/4) = (1/2) × (4/3) = 4/6 = 2/3
Therefore, (-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4) simplifies to 2/3.
First, let's simplify the multiplication:
(-2) × (1/5) × (-5/6) = (-2) × (-1) × (1/5) × (5/6) = 2/6 = 1/3
Now, let's solve the division:
(1/3) ÷ (2/3) ÷ (3/4)
By using the division property, we can perform the divisions from left to right:
(1/3) ÷ (2/3) = (1/3) × (3/2) = 3/6 = 1/2
(1/2) ÷ (3/4) = (1/2) × (4/3) = 4/6 = 2/3
Therefore, (-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4) simplifies to 2/3.
clarify the sign
Apologies for the confusion. Let's clarify the signs in the expression:
(-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4)
To solve this expression, we'll follow the properties of operations and rules for multiplying and dividing.
First, let's simplify the multiplication:
(-2) × (1/5) × (-5/6) = 2/5 × 5/6 = 10/30 = 1/3
Now, let's solve the division:
(1/3) ÷ (2/3) ÷ (3/4)
By using the division property, we can perform the divisions from left to right:
(1/3) ÷ (2/3) = (1/3) × (3/2) = 3/6 = 1/2
(1/2) ÷ (3/4) = (1/2) × (4/3) = 4/6 = 2/3
Therefore, (-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4) simplifies to -2/3.
(-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4)
To solve this expression, we'll follow the properties of operations and rules for multiplying and dividing.
First, let's simplify the multiplication:
(-2) × (1/5) × (-5/6) = 2/5 × 5/6 = 10/30 = 1/3
Now, let's solve the division:
(1/3) ÷ (2/3) ÷ (3/4)
By using the division property, we can perform the divisions from left to right:
(1/3) ÷ (2/3) = (1/3) × (3/2) = 3/6 = 1/2
(1/2) ÷ (3/4) = (1/2) × (4/3) = 4/6 = 2/3
Therefore, (-2) × (1/5) ÷ (2/3) × (-5/6) ÷ (3/4) simplifies to -2/3.
Use the properties of operations and rules for multiplying and dividing to solve:
(9)÷(5/4)×(7/9)×(−5)÷(7/2)
Responses
−1,225/8
negative Start Fraction 1,225 over 8 End Fraction
8
−8
1,225/8
(9)÷(5/4)×(7/9)×(−5)÷(7/2)
Responses
−1,225/8
negative Start Fraction 1,225 over 8 End Fraction
8
−8
1,225/8
To solve this expression, we can apply the properties of operations and rules for multiplying and dividing. Let's simplify it step by step:
First, let's simplify the division:
(9) ÷ (5/4) = (9) × (4/5) = 36/5
Next, let's simplify the multiplication:
(36/5) × (7/9) × (-5) ÷ (7/2) = (36/5) × (7/9) × (-5) × (2/7)
Notice that the factors of 7/9 and 2/7 cancel each other out:
(36/5) × (7/9) × (-5) × (2/7) = (36/5) × (1/1) × (-5) × (1/1) = (36/5) × (-5)
Now, let's multiply:
(36/5) × (-5) = -180/5 = -36
Therefore, (9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2) simplifies to -36.
First, let's simplify the division:
(9) ÷ (5/4) = (9) × (4/5) = 36/5
Next, let's simplify the multiplication:
(36/5) × (7/9) × (-5) ÷ (7/2) = (36/5) × (7/9) × (-5) × (2/7)
Notice that the factors of 7/9 and 2/7 cancel each other out:
(36/5) × (7/9) × (-5) × (2/7) = (36/5) × (1/1) × (-5) × (1/1) = (36/5) × (-5)
Now, let's multiply:
(36/5) × (-5) = -180/5 = -36
Therefore, (9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2) simplifies to -36.
use the options I gave you
Apologies for the confusion. Let's solve the expression using the given options:
(9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2)
Using the given options:
Option 1: -1,225/8
Option 2: negative Start Fraction 1,225 over 8 End Fraction
Option 3: 8
Option 4: -8
Option 5: 1,225/8
To solve this expression, we'll perform the calculations step by step:
First, let's simplify the division:
(9) ÷ (5/4) = (9) × (4/5) = 36/5
Next, let's simplify the multiplication:
(36/5) × (7/9) × (-5) ÷ (7/2) = (36/5) × (7/9) × (-5) × (2/7)
Notice that the factors of 7 cancel each other out:
(36/5) × (7/9) × (-5) × (2/7) = (36/5) × (1/1) × (-5) × (1/1) = (36/5) × (-5)
Now, let's multiply:
(36/5) × (-5) = -180/5 = -36
Therefore, the result of the expression, using the given options, is not any of the provided choices. It simplifies to -36.
(9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2)
Using the given options:
Option 1: -1,225/8
Option 2: negative Start Fraction 1,225 over 8 End Fraction
Option 3: 8
Option 4: -8
Option 5: 1,225/8
To solve this expression, we'll perform the calculations step by step:
First, let's simplify the division:
(9) ÷ (5/4) = (9) × (4/5) = 36/5
Next, let's simplify the multiplication:
(36/5) × (7/9) × (-5) ÷ (7/2) = (36/5) × (7/9) × (-5) × (2/7)
Notice that the factors of 7 cancel each other out:
(36/5) × (7/9) × (-5) × (2/7) = (36/5) × (1/1) × (-5) × (1/1) = (36/5) × (-5)
Now, let's multiply:
(36/5) × (-5) = -180/5 = -36
Therefore, the result of the expression, using the given options, is not any of the provided choices. It simplifies to -36.
wrong
Apologies for the mistake. Let's solve the expression again using the given options. The expression is:
(9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2)
Using the given options:
Option 1: -1,225/8
Option 2: negative Start Fraction 1,225 over 8 End Fraction
Option 3: 8
Option 4: -8
Option 5: 1,225/8
To simplify the expression, we'll follow the properties of operations and rules for multiplying and dividing:
First, let's simplify the division:
(9) ÷ (5/4) = (9) × (4/5) = 36/5
Next, let's simplify the multiplication:
(36/5) × (7/9) × (-5) ÷ (7/2) = (36/5) × (7/9) × (-5) × (2/7)
The factor of 7 cancels out:
(36/5) × (7/9) × (-5) × (2/7) = (36/5) × (1/9) × (-5) × (2/1)
Multiplying the fractions:
(36/5) × (1/9) = 36/45 = 4/5
Now, continuing with the multiplication and division:
(4/5) × (-5) = -20/5 = -4
Finally, dividing by (7/2):
-4 ÷ (7/2) = -4 × (2/7) = -8/7
Therefore, the expression simplifies to -8/7. Looking at the options provided, the correct answer is not listed.
(9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2)
Using the given options:
Option 1: -1,225/8
Option 2: negative Start Fraction 1,225 over 8 End Fraction
Option 3: 8
Option 4: -8
Option 5: 1,225/8
To simplify the expression, we'll follow the properties of operations and rules for multiplying and dividing:
First, let's simplify the division:
(9) ÷ (5/4) = (9) × (4/5) = 36/5
Next, let's simplify the multiplication:
(36/5) × (7/9) × (-5) ÷ (7/2) = (36/5) × (7/9) × (-5) × (2/7)
The factor of 7 cancels out:
(36/5) × (7/9) × (-5) × (2/7) = (36/5) × (1/9) × (-5) × (2/1)
Multiplying the fractions:
(36/5) × (1/9) = 36/45 = 4/5
Now, continuing with the multiplication and division:
(4/5) × (-5) = -20/5 = -4
Finally, dividing by (7/2):
-4 ÷ (7/2) = -4 × (2/7) = -8/7
Therefore, the expression simplifies to -8/7. Looking at the options provided, the correct answer is not listed.
simplify it
Apologies for the confusion. Let's simplify the expression again:
To start, let's simplify the division:
(9) ÷ (5/4) = (9) × (4/5) = 36/5
Now, let's solve the multiplication and division:
(36/5) × (7/9) × (-5) ÷ (7/2)
By using the multiplication property and canceling out the common factors:
= (36/5) × (7/9) × (-5) × (2/7)
= (36/5) × (2/9) × (-5)
= (72/45) × (-5)
= -8/5 × (-5)
= 40/5
= 8
Therefore, the expression simplifies to 8.
To start, let's simplify the division:
(9) ÷ (5/4) = (9) × (4/5) = 36/5
Now, let's solve the multiplication and division:
(36/5) × (7/9) × (-5) ÷ (7/2)
By using the multiplication property and canceling out the common factors:
= (36/5) × (7/9) × (-5) × (2/7)
= (36/5) × (2/9) × (-5)
= (72/45) × (-5)
= -8/5 × (-5)
= 40/5
= 8
Therefore, the expression simplifies to 8.
can you clarify the sign
Apologies for the confusion. Let's clarify the signs in the expression:
(9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2)
To solve this expression, we'll follow the properties of operations and rules for multiplying and dividing.
First, let's simplify the division:
(9) ÷ (5/4) = (9) × (4/5) = 36/5
Next, let's solve the multiplication:
(36/5) × (7/9) × (-5) ÷ (7/2) = (36/5) × (7/9) × (-5) × (2/7)
Notice that the factors of 7 cancel each other out:
(36/5) × (7/9) × (-5) × (2/7) = (36/5) × (1/1) × (-5) × (1/1) = (36/5) × (-5)
Now, let's multiply:
(36/5) × (-5) = -180/5 = -36
Therefore, the simplified expression is -36.
(9) ÷ (5/4) × (7/9) × (-5) ÷ (7/2)
To solve this expression, we'll follow the properties of operations and rules for multiplying and dividing.
First, let's simplify the division:
(9) ÷ (5/4) = (9) × (4/5) = 36/5
Next, let's solve the multiplication:
(36/5) × (7/9) × (-5) ÷ (7/2) = (36/5) × (7/9) × (-5) × (2/7)
Notice that the factors of 7 cancel each other out:
(36/5) × (7/9) × (-5) × (2/7) = (36/5) × (1/1) × (-5) × (1/1) = (36/5) × (-5)
Now, let's multiply:
(36/5) × (-5) = -180/5 = -36
Therefore, the simplified expression is -36.
Solve this multi-step problem. A runner completes 14 of a 5-mile race every 8 minutes. At the same pace, how far can the runner go in 16 minutes?
Responses
110 mile
160 miles
212 miles
18 mile
Responses
110 mile
160 miles
212 miles
18 mile
To solve this problem, we can set up a ratio using the information given.
The runner completes 14 miles in 8 minutes. This can be represented as 14 miles / 8 minutes.
We need to find how far the runner can go in 16 minutes, so we set up a new ratio using the information given:
14 miles / 8 minutes = x miles / 16 minutes
To find x, we can cross multiply:
(14 miles)(16 minutes) = (8 minutes)(x miles)
224 miles = 8x
To solve for x, we divide both sides of the equation by 8:
224 miles / 8 = x
28 miles = x
Therefore, at the same pace, the runner can go 28 miles in 16 minutes.
Looking at the options provided, none of the choices listed match the correct answer of 28 miles.
The runner completes 14 miles in 8 minutes. This can be represented as 14 miles / 8 minutes.
We need to find how far the runner can go in 16 minutes, so we set up a new ratio using the information given:
14 miles / 8 minutes = x miles / 16 minutes
To find x, we can cross multiply:
(14 miles)(16 minutes) = (8 minutes)(x miles)
224 miles = 8x
To solve for x, we divide both sides of the equation by 8:
224 miles / 8 = x
28 miles = x
Therefore, at the same pace, the runner can go 28 miles in 16 minutes.
Looking at the options provided, none of the choices listed match the correct answer of 28 miles.
can you use the responses i gave you
Apologies for the confusion. Let's solve the problem using the given responses:
We know that the runner completes 14 miles in 8 minutes.
To find how far the runner can go in 16 minutes, we can set up a proportion:
14 miles / 8 minutes = x miles / 16 minutes
Cross multiplying, we get:
14 * 16 = 8 * x
224 = 8x
Dividing both sides by 8:
224/8 = x
28 = x
Therefore, the runner can go 28 miles in 16 minutes.
Looking at the given responses, the correct answer is not among the options provided.
We know that the runner completes 14 miles in 8 minutes.
To find how far the runner can go in 16 minutes, we can set up a proportion:
14 miles / 8 minutes = x miles / 16 minutes
Cross multiplying, we get:
14 * 16 = 8 * x
224 = 8x
Dividing both sides by 8:
224/8 = x
28 = x
Therefore, the runner can go 28 miles in 16 minutes.
Looking at the given responses, the correct answer is not among the options provided.
simplify it
Apologies for the confusion. Let's simplify the problem:
If the runner completes 14 miles in 8 minutes, we can find their speed by dividing the distance by the time:
Speed = 14 miles / 8 minutes = 1.75 miles per minute
Now, we can determine how far the runner can go in 16 minutes by multiplying their speed by the time:
Distance = 1.75 miles per minute * 16 minutes = 28 miles
Therefore, at the same pace, the runner can go 28 miles in 16 minutes.
If the runner completes 14 miles in 8 minutes, we can find their speed by dividing the distance by the time:
Speed = 14 miles / 8 minutes = 1.75 miles per minute
Now, we can determine how far the runner can go in 16 minutes by multiplying their speed by the time:
Distance = 1.75 miles per minute * 16 minutes = 28 miles
Therefore, at the same pace, the runner can go 28 miles in 16 minutes.
use fractions
Sure! Let's solve the problem using fractions.
If the runner completes 14 miles in 8 minutes, we can find their speed by dividing the distance by the time:
Speed = 14 miles / 8 minutes
To simplify this, we can reduce the fraction:
Speed = (7/4) miles per minute
Now, we can determine how far the runner can go in 16 minutes by multiplying their speed by the time:
Distance = (7/4) miles per minute * 16 minutes
To simplify this, we can multiply the numerators and the denominators:
Distance = (7 * 16) / (4 * 1) miles
Distance = 112/4 miles
To simplify this fraction, we can divide the numerator and the denominator by their greatest common divisor, which is 4:
Distance = 28 miles
Therefore, at the same pace, the runner can go 28 miles in 16 minutes.
If the runner completes 14 miles in 8 minutes, we can find their speed by dividing the distance by the time:
Speed = 14 miles / 8 minutes
To simplify this, we can reduce the fraction:
Speed = (7/4) miles per minute
Now, we can determine how far the runner can go in 16 minutes by multiplying their speed by the time:
Distance = (7/4) miles per minute * 16 minutes
To simplify this, we can multiply the numerators and the denominators:
Distance = (7 * 16) / (4 * 1) miles
Distance = 112/4 miles
To simplify this fraction, we can divide the numerator and the denominator by their greatest common divisor, which is 4:
Distance = 28 miles
Therefore, at the same pace, the runner can go 28 miles in 16 minutes.
Solve this multi-step problem. A runner completes 1/4 of a 5-mile race every 8 minutes. At the same pace, how far can the runner go in 16 minutes?
1/10 mile
160 miles
2 1/2 miles
1/8 mile
1/10 mile
160 miles
2 1/2 miles
1/8 mile
To solve this problem, we can set up a proportion using the information given:
The runner completes 1/4 of a 5-mile race in 8 minutes. This can be represented as (1/4) mile / 8 minutes.
To find how far the runner can go in 16 minutes, we set up a new proportion:
(1/4) mile / 8 minutes = x miles / 16 minutes
To find x, we can cross multiply:
(1/4) mile * 16 minutes = 8 minutes * x miles
4 miles = 8x
To solve for x, we divide both sides of the equation by 8:
4 miles / 8 = x
1/2 mile = x
Therefore, at the same pace, the runner can go 1/2 mile in 16 minutes.
Looking at the options provided, the correct answer is not among the choices.
The runner completes 1/4 of a 5-mile race in 8 minutes. This can be represented as (1/4) mile / 8 minutes.
To find how far the runner can go in 16 minutes, we set up a new proportion:
(1/4) mile / 8 minutes = x miles / 16 minutes
To find x, we can cross multiply:
(1/4) mile * 16 minutes = 8 minutes * x miles
4 miles = 8x
To solve for x, we divide both sides of the equation by 8:
4 miles / 8 = x
1/2 mile = x
Therefore, at the same pace, the runner can go 1/2 mile in 16 minutes.
Looking at the options provided, the correct answer is not among the choices.
A water tank decreases by 10 gallons every 3 hours every day. What is the total change in the amount of water in the tank after 6 days?
To find the total change in the amount of water in the tank after 6 days, we need to determine the change in water each day and then multiply it by the number of days.
We know that the water tank decreases by 10 gallons every 3 hours every day.
To find the change in water each day, we need to calculate how many times 3 hours occurs in a day:
24 hours in a day / 3 hours = 8 times
So, the water tank will decrease by 10 gallons 8 times each day.
Therefore, the change in water each day is:
10 gallons x 8 = 80 gallons
To find the total change in water after 6 days, we multiply the change in water each day by the number of days:
80 gallons x 6 days = 480 gallons
Therefore, the total change in the amount of water in the tank after 6 days is 480 gallons.
We know that the water tank decreases by 10 gallons every 3 hours every day.
To find the change in water each day, we need to calculate how many times 3 hours occurs in a day:
24 hours in a day / 3 hours = 8 times
So, the water tank will decrease by 10 gallons 8 times each day.
Therefore, the change in water each day is:
10 gallons x 8 = 80 gallons
To find the total change in water after 6 days, we multiply the change in water each day by the number of days:
80 gallons x 6 days = 480 gallons
Therefore, the total change in the amount of water in the tank after 6 days is 480 gallons.
clarify the sign please
Apologies for the confusion. Let's clarify the sign in the problem:
A water tank decreases by 10 gallons every 3 hours every day.
To find the total change in the amount of water in the tank after 6 days, we need to determine the change in water each day and then multiply it by the number of days.
Since the tank is decreasing by 10 gallons, the change in water each day would be -10 gallons.
Therefore, the total change in water after 6 days would be:
-10 gallons x 6 days = -60 gallons
Therefore, the total change in the amount of water in the tank after 6 days is a decrease of 60 gallons.
A water tank decreases by 10 gallons every 3 hours every day.
To find the total change in the amount of water in the tank after 6 days, we need to determine the change in water each day and then multiply it by the number of days.
Since the tank is decreasing by 10 gallons, the change in water each day would be -10 gallons.
Therefore, the total change in water after 6 days would be:
-10 gallons x 6 days = -60 gallons
Therefore, the total change in the amount of water in the tank after 6 days is a decrease of 60 gallons.
I said clarify the damn sign not change ur entire answer
Apologies for the misunderstanding. Let's clarify the sign without changing the answer:
A water tank decreases by 10 gallons every 3 hours every day.
To find the total change in the amount of water in the tank after 6 days, we need to determine the change in water each day and then multiply it by the number of days.
Since the tank is decreasing by 10 gallons, the change in water each day would be -10 gallons (negative sign indicating a decrease).
Therefore, the total change in water after 6 days would be:
-10 gallons x 6 days = -60 gallons
Therefore, the total change in the amount of water in the tank after 6 days is a decrease of 60 gallons.
A water tank decreases by 10 gallons every 3 hours every day.
To find the total change in the amount of water in the tank after 6 days, we need to determine the change in water each day and then multiply it by the number of days.
Since the tank is decreasing by 10 gallons, the change in water each day would be -10 gallons (negative sign indicating a decrease).
Therefore, the total change in water after 6 days would be:
-10 gallons x 6 days = -60 gallons
Therefore, the total change in the amount of water in the tank after 6 days is a decrease of 60 gallons.
A water tank decreases by 10 gallons every 3 hours every day. What is the total change in the amount of water in the tank after 6 days?
clarify the sign
clarify the sign
Apologies for the confusion. Let's clarify the sign in the problem:
A water tank decreases by 10 gallons every 3 hours every day.
To find the total change in the amount of water in the tank after 6 days, we need to determine the change in water each day and then multiply it by the number of days.
Since the tank is decreasing by 10 gallons, the change in water each day would be -10 gallons (negative sign indicating a decrease).
Therefore, the total change in water after 6 days would be:
-10 gallons/day x 6 days = -60 gallons
Therefore, the total change in the amount of water in the tank after 6 days is a decrease of 60 gallons.
A water tank decreases by 10 gallons every 3 hours every day.
To find the total change in the amount of water in the tank after 6 days, we need to determine the change in water each day and then multiply it by the number of days.
Since the tank is decreasing by 10 gallons, the change in water each day would be -10 gallons (negative sign indicating a decrease).
Therefore, the total change in water after 6 days would be:
-10 gallons/day x 6 days = -60 gallons
Therefore, the total change in the amount of water in the tank after 6 days is a decrease of 60 gallons.
all of the bots answers are wrong here are the actual answers if you still needed it
1. 2/3
2.-8
3.2 1/2
4.-480
5.1/3 x 150 (divided by) 4
i hope this helps! :)
1. 2/3
2.-8
3.2 1/2
4.-480
5.1/3 x 150 (divided by) 4
i hope this helps! :)